2020
DOI: 10.25035/ijare.13.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lifeguards’ Hazard Detection and Eye Movements with Experience: Is One Season Enough?

Abstract: Surveillance is key to the lifesaving capability of lifeguards. Experienced personnel consistently display enhanced hazard detection capabilities compared to less experienced counterparts. However, the mechanisms which underpin this effect and the time it takes to develop these skills are not understood. We hypothesized that, after one season of experience, the number of hazards detected by, and eye movements of, less experienced lifeguards (LEL) would more closely approximate experienced lifeguards (EL). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Previous research exploring lifeguard drowning detection found differences between lifeguards and non‐lifeguards in their detection accuracy and response times (Laxton & Crundall, 2018). However, the eye‐movements of lifeguards and non‐lifeguards do not necessarily reflect this detection superiority (Laxton et al, 2020; Laxton et al, 2021; Smith et al, 2020). In both the Laxton et al (2020) and Laxton et al (2021) studies there was a suggestion that small non‐significant gains in both the time to first fixate the target, and the amount of processing time required, added up to produce a significant superiority in response times to drowning targets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research exploring lifeguard drowning detection found differences between lifeguards and non‐lifeguards in their detection accuracy and response times (Laxton & Crundall, 2018). However, the eye‐movements of lifeguards and non‐lifeguards do not necessarily reflect this detection superiority (Laxton et al, 2020; Laxton et al, 2021; Smith et al, 2020). In both the Laxton et al (2020) and Laxton et al (2021) studies there was a suggestion that small non‐significant gains in both the time to first fixate the target, and the amount of processing time required, added up to produce a significant superiority in response times to drowning targets.…”
Section: Introductionmentioning
confidence: 99%
“…Each variation of these methodologies introduces variations in terms of task representativeness (i.e., the fidelity with which tasks emulate real-world conditions), complexity, and duration. It is unsurprising that these methodological divergences have emerged as pivotal contributors to the inconsistent findings witnessed within the literature on lifeguard drowning detection(Smith, 2016;Smith et al, 2020), a trend that continues in the present study. The evaluation of lifeguards' direct performance in detecting drownings is inherently constrained when attempting to incorporate uncontrollable scenarios marked by contextual variations.…”
mentioning
confidence: 75%
“…A diverse range of methodologies has been employed to assess the effectiveness of lifeguards in detecting drowning incidents, from pre‐recorded CCTV footage (Lanagan‐Leitzel, 2012) to scripted beach recordings (Smith et al, 2020). Each variation of these methodologies introduces variations in terms of task representativeness (i.e., the fidelity with which tasks emulate real‐world conditions), complexity, and duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations